ROR1 contributes to melanoma cell growth and migration by regulating N‐cadherin expression via the PI3K/Akt pathway. Issue 11 (28th October 2015) - Fernández, Natalia Brenda; Lorenzo, Daniela; Picco, María Elisa; Barbero, Gastón; Dergan‐Dylon, Leonardo Sebastián; Marks, María Paula; García‐Rivello, Hernán; Gimenez, Liliana; Labovsky, Vivian; Grumolato, Luca; Lopez‐Bergami, Pablo
Abstract : The Receptor tyrosine kinase‐like Orphan Receptor 1 (ROR1) is primarily expressed by neural crest cells during embryogenesis. Following a complete downregulation after birth, ROR1 was shown to re‐express in various types of cancers. Little is known about ROR1 expression and function in melanoma. Here we show that ROR1 is aberrantly expressed in both melanoma cell lines and tumors and that its expression associates with poor Post‐Recurrence Survival of melanoma. Using gain‐ and loss‐of‐function approaches we found that ROR1 enhances both anchorage‐dependent and ‐independent growth of melanoma cells. In addition, ROR1 decreases cell adhesion and increases cell motility and migration. Mechanistically, ROR1 was found to induce upregulation of Akt and the mesenquimal markers N‐cadherin and vimentin. The regulation of N‐cadherin by ROR1 relies on both Akt dependent and independent mechanisms. ROR1 does not affect Wnt canonical pathway but was found to be engaged in a positive feedback loop with Wnt5a. In summary, we show that ROR1 contributes to melanoma progression and is a candidate biomarker of poor prognosis. Although further studies are needed to confirm this possibility, the present work indicates that ROR1 is a good prospective target for melanoma cancer therapy. © 2015 Wiley Periodicals, Inc.